1989
DOI: 10.1021/bi00446a007
|View full text |Cite
|
Sign up to set email alerts
|

Flavin and heme structures in lactate: cytochrome c oxidoreductase: a resonance Raman study

Abstract: Resonance Raman spectra of Hansenula anomala L-lactate:cytochrome c oxidoreductase (or flavocytochrome b2), of its cytochrome b2 core, and of a bis(imidazole) iron-protoporphyrin complex were obtained at the Soret preresonance from the oxidized and reduced forms. Raman contributions from both the isoalloxazine ring of flavin mononucleotide (FMN) and the heme b2 were observed in the spectra of oxidized flavocytochrome b2. Raman diagrams showing frequency differences of selected FMN modes between aqueous and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 75 publications
6
55
0
Order By: Relevance
“…Our study shows frequencies close to those published in the study of Schmidt et al (24). With reference to the RR frequencies of FAD in water, Raman diagrams were previously drawn to visualize the apoprotein effect on the high frequency modes of the isoalloxazine ring (19,26). In the diagram of oxidized GR (Fig.…”
Section: Rr Spectra Of the E Ox Eh 2 And Mds Species Of Yeast Grsupporting
confidence: 55%
See 1 more Smart Citation
“…Our study shows frequencies close to those published in the study of Schmidt et al (24). With reference to the RR frequencies of FAD in water, Raman diagrams were previously drawn to visualize the apoprotein effect on the high frequency modes of the isoalloxazine ring (19,26). In the diagram of oxidized GR (Fig.…”
Section: Rr Spectra Of the E Ox Eh 2 And Mds Species Of Yeast Grsupporting
confidence: 55%
“…In the diagram of oxidized GR (Fig. 5), the frequency shifts detected for GR are generally negative, indicating an electron-deficient isoalloxazine ring (19,26). The shapes of the Raman diagrams were associated with the electron distribution through the three rings of the isoalloxazine moiety and correlated with the biological activities of several flavoproteins (19,26).…”
Section: Rr Spectra Of the E Ox Eh 2 And Mds Species Of Yeast Grmentioning
confidence: 95%
“…OH (492 cm-l; Asher and Schuster, 1979;Asher et al, 1977) and Mb Fe(II1) . OH (491 cin '; Asher and Schuster, 1979 ;Asher et al, 1977 ;Desbois et al, 1979) and slightly lower than the value (503 cm-') reported for the low-spin horseradish peroxidase Fe(II1) I OH complex (Sitter et al, 1988). Isotopic substitution of H,'"O by H2"0 does not allow discrimination between -OH, which should produce a shift from 489 cm-' to 469 cm ', and HZO, which should produce a shift from 489 cm-' to 470 cm-'.…”
Section: Coordination State Of Fe In Native Pghs Fe(ii1)mentioning
confidence: 56%
“…2B), showing that the heme iron of cyt p30 is coordinated with the imidazole moiety of two histidyl residues, as in cyt h, and cyt h, (Kitagawa et al, 1982;Desbois et al, 1989;Silvestrini et al, 1993). Cytochrome h-562, in which the heme is coordinated by HislMet residues, exhibits a o,, mode at a significantly higher frequency (1548 cm-'; Bullock and Myers, 1978; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is interesting to note that the HS heme of cyt p30 Selected porphyrin modes of ferric cytochromes b and model complexes. bZ, Desbois et al (1989); Silvestrini et al (1993);b-562, Bullock and Myer (1978); FePP(Im),, imidazole and imidazolate complexes of Fe(I1)-protoporphyrin Desbois and Lutz, 1992); MbF, fluoro-, and Mb(H20) aquo-metmyoglobin, and FePP(MeZSO),, bis(dimethylsu1foxide) complex of Fe(II1)-protoporphyrin Andersson et al, 1985); FePP(CI), chloride complex of Fe(II1)-protoporphyrin Desbois et al (1989); Silvestrini et al (1993);b-562, Bullock and Myer (1978); FePP(Im),, imidazole and imidazolate complexes of Fe(I1)-protoporphyrin Desbois and Lutz, 1992); FePP(2MeIm), 2-methylimidazole, 2-methylimidazolate, and FePP(His), histidine and histidinate complexes of Fe(I1)-protoporphyrin Othman et al, 1993, and unpublished spectra (Ozaki et al, 1986). Since there is no evidence for an electronic transition in the 600-700-nm region of absorption spectra of cyt p30, the HS heme cannot be associated with an Fe-chlorin.…”
Section: Resultsmentioning
confidence: 99%